Causes of Orthodontic Pain & its treatment: an overview (Update Dental College Journal, 2016)
Orthodontic pain, the most cited negative effect arising as a result of orthodontic force application, is a major matter of distress for clinicians and patients/parents and directly influences their compliance during the treatment. The lengthy duration of treatment along with frequent pain due to the orthodontic appliances often leads to patient burn out and has been associated with discontinuation of orthodontic treatment. It is imperative for the clinicians to identify and manage the pain experienced by their patients. It becomes duty of an orthodontist to satisfy the questions arising in the mind of patients, parents and clinicians. Various modalities for the management of orthodontic pain have been proposed over the years. The purpose of this review article is to throw a light on the various possible causes of orthodontic pain and to discuss the various management options for the orthodontic pain.Update Dent. Coll. j: 2016; 6 (1): 43-51